2023
DOI: 10.3233/jpd-223564
|View full text |Cite
|
Sign up to set email alerts
|

Increased Effective Connectivity of the Left Parietal Lobe During Walking Tasks in Parkinson’s Disease

Abstract: Background: In Parkinson’s disease (PD), walking may depend on the activation of the cerebral cortex. Understanding the patterns of interaction between cortical regions during walking tasks is of great importance. Objective: This study investigated differences in the effective connectivity (EC) of the cerebral cortex during walking tasks in individuals with PD and healthy controls. Methods: We evaluated 30 individuals with PD (62.4±7.2 years) and 22 age-matched healthy controls (61.0±6.4 years). A mobile funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Critically, one study regarding attention deficits reported increased centrality of the PL in attention‐deficit/hyperactivity disorder patients 35 . In a PD patients walking research, it also showed that increased effective connectivity of the parietal lobe of PD patients played a compensatory role 36 . Yet, whether the IPL exists as an abnormal functional connection in PD‐low‐GDNF subjects remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, one study regarding attention deficits reported increased centrality of the PL in attention‐deficit/hyperactivity disorder patients 35 . In a PD patients walking research, it also showed that increased effective connectivity of the parietal lobe of PD patients played a compensatory role 36 . Yet, whether the IPL exists as an abnormal functional connection in PD‐low‐GDNF subjects remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In a PD patients walking research, it also showed that increased effective connectivity of the parietal lobe of PD patients played a compensatory role. 36 Yet, whether the IPL exists as an abnormal functional connection in PD‐low‐GDNF subjects remains unknown. One possibility is that an improperly connected IPL hub disrupts neural systems during task performance in real life, thereby causing impairments in executive functioning, including attention and working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research focusing on cortical activation patterns in relation to gait adaptability, hemodynamic responses, and obstacle negotiation offers additional insights [ 24 - 26 ]. For instance, Pelicionie et al (2022) examined how patients with PD adjust their gait in response to varying walking conditions, such as changing speeds or avoiding obstacles, and found that these patients exhibit altered cortical activation, particularly in brain regions associated with motor planning and execution, during gait adaptability tasks.…”
Section: Methodsmentioning
confidence: 99%